VD_FINDINFO HC / 2024 / 594 vom 14. August 2024 - VD Tribunal cantonal (2024)
EXPULSION DE LOCATAIRE, PROCÉDURE SOMMAIRE, DÉLAI, RETARD, DÉCISION D'IRRECEVABILITÉ | 138 al. 3 let. a CPC (CH), 314 al. 1 CPC (CH)